2014
DOI: 10.1021/jp507552q
|View full text |Cite
|
Sign up to set email alerts
|

Computational and Experimental Characterization of a Fluorescent Dye for Detection of Potassium Ion Concentration

Abstract: The fluorescence of the SKC-513 ((E)-N-(9-(4-(1,4,7,10,13-pentaoxa-16-azacyclooctadecan-16-yl)phenyl)-6-(butyl(3-sulfopropyl)amino)-3H-xanthen-3-ylidene)-N-(3-sulfopropyl)butan-1-aminium) dye is shown experimentally to have high sensitivity to binding of the K+ ion. Computations are used to explore the potential origins of this sensitivity and to make some suggestions regarding structural improvements. In the absence of K+, excitation is to two nearly degenerate states, a neutral (N) excited state with a high … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…These macrocycles, along with Ca 2+ and pH sensors, were incorporated into a multianalyte microfluidic device that was used for the analysis of the electrolytes present in human tears. Potassium was detected by rhodamine-appended 163 (Figure ), and computational studies indicated that 163 was a PET-based sensor, in which complexation with K + destabilized the charge transfer state, leading to the observed signal changes Figure ), containing a europium luminophore appendage, was used to detect potassium in synthetic human blood serum …”
Section: Luminescent Macrocycle Sensorsmentioning
confidence: 99%
“…These macrocycles, along with Ca 2+ and pH sensors, were incorporated into a multianalyte microfluidic device that was used for the analysis of the electrolytes present in human tears. Potassium was detected by rhodamine-appended 163 (Figure ), and computational studies indicated that 163 was a PET-based sensor, in which complexation with K + destabilized the charge transfer state, leading to the observed signal changes Figure ), containing a europium luminophore appendage, was used to detect potassium in synthetic human blood serum …”
Section: Luminescent Macrocycle Sensorsmentioning
confidence: 99%
“…[6][7][8] A sodium-potassium pump that moves both Na + and K + in opposite directions across the plasma membrane is responsible for the mechanism of the ion transportation. [8][9][10][11][12][13] The concentrations of Na + and K + on the opposite sides of the membrane are interdependent, suggesting that the same carrier transports both the ions. On the other hand, Mg 2+ and Ca 2+ play key roles in nerve transmission, maintenance of muscular strength and extracellular osmolarity, enzyme activation, apoptosis of a cell, regulation of blood pressure, pH, and the concentration of other ions in living cells.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8] Nucleic acid-based aptamers that are generated by a systematic evolution of ligands with an exponential enrichment (SELEX) process and obtained through selections, 9 are artificial single-stranded DNA (ssDNA) or RNA sequences that can recognize specific biological molecules with a wide range, such as small molecules, 10 organic compound, 11 proteins 12 or even whole cells. 13 With outstanding stability, high affinity, excellent selectivity, easy modification, as well as low immunogenesis, nucleic acid-based aptamers have successfully attracted the increasing attention of researchers, and have been widely used in food safety, diagnosis, cell imaging and drug delivery.…”
Section: Introductionmentioning
confidence: 99%